Kontribusi Prodi Pendidikan dan Pengajaran Agama Katolik STAKat Negeri Pontianak dengan Dunia Kerja - Herkulanus Pongkot; Martinus Martinus; Mukarramah Mukarramah (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
This is a study of the situation of alumni, especially in terms of job search, work situations and the use of competency acquisition during college. The purpose of this activity is to collect relevant information and input from graduates related to the